Cultural Beliefs of Zulu Women During Pregnancy, Labour, and Postnatal Infant Care in the KwaZulu-Natal Province of South Africa - Mmbulaheni Ramulondi (Africa Journal of Nursing and Midwifery, 2026)
Numerous ongoing cultural beliefs begin at birth and continue throughout various stages of life. Women continue to observe these beliefs not only because they are traditions, but also because they hold meaning for them. This study explores the cultural beliefs and practices of Zulu women during childbirth. One hundred and forty women living in northern Maputaland were purposively selected and interviewed. Descriptive statistics were used to analyse data. The results indicated that all participants in this study were aware of and observed behavioural taboos during childbearing. Furthermore, 63% of the participants observed practices based on spiritual belief. The most widely observed behaviour taboo during pregnancy is that pregnant women are not allowed to attend funerals, while the most cited spiritual ritual is tying a string, given by the church or traditional healer, around the waist as a form of protection for pregnant women. The most practised ritual is that pregnant women burn a herbal plant (impepho) while in labour. After delivery, the most widely performed ritual is tying a goat’s skin (isiphandla) around the newborn baby’s hand. While cultural practices related to pregnancy, labour, and postnatal infant care continue to be observed in Zulu society, it is essential to identify and promote good practices while discouraging harmful ones. Understanding the beliefs and practices of rural Zulu women from a cultural perspective will enable healthcare workers to provide culturally sensitive care and support, thereby improving maternal and child health.